Starch granule size distribution in caryopses of selected malting varieties of spring barley - Psota, Vratislav; Bohačenko, Ivan; Chmelík, Josef; Hartmann, Jiří (BrewingScience, 2004)
In ten varieties of spring barley (Hordeum vulgare L.) of Czech, Slovak, and German origin, starch granule size distribution in a caryopsis endosperm was followed for a three-year period by means of the Low Angle Laser Light Scattering Method (LLALS). Distinct intervarietal differences were detected in starch granule size distribution. A share of the varieties in starch granule size distribution variability was 70%. Effects of growing localities (12 %) and years (6 %) did not play a significant role. According to a ratio of large starch granules the varieties could be split into three groups. The varieties Akcent, Forum, and Atribut had the highest ratio of large starch granules, the varieties Krona, Tolar, Amulet, Olbram, and Novum had the lowest. Increase in small starch granule content was accompanied with reduction of values of relative extract at 45 °C, wort viscosity, germination index, β-glucans in barley, in malt and wort and prolongation of saccharification time and increase of values of homogeneity and malt modification by the Carlsberg method. However, among the followed technological parameters and starch granule size distribution, there was only a low statistical dependence.